2005
DOI: 10.1667/rr3439.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Treatment Decreases Bone Cancer Pain through Direct Effect on Tumor Cells

Abstract: The most used treatment for bone cancer pain is radiation; however, the mechanism responsible for analgesia after irradiation is unknown. The mechanistic influence of a single, localized 10-, 20- or 30-Gy dose of radiation on painful behaviors, osteolysis, histopathology and osteoclast number was evaluated in mice with painful femoral sarcomas. Dramatic reductions in pain behaviors (P < 0.05) and osteolysis (P < 0.0001) were seen in mice irradiated with 20 and 30 Gy. Irradiation reduced the tumor area by more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…No improvement in behavioral measures of bone cancer pain was seen in mice receiving 5-FC alone, radiotherapy alone, or 5-FC with radiation treatment. Previous study of painful bone cancers has shown that reductions in bone cancer pain from sarcoma, melanoma, and colon adenocarcinoma tumors are associated with treatments that inhibit cancer-induced osteolysis and reduce tumor burden (19,20,25,26,34). Surprisingly, in this investigation, radiation treatment alone and CD/5-FC therapy combined with radiation significantly reduced breast cancer -induced osteolysis and tumor burden but did not influence pain behaviors.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…No improvement in behavioral measures of bone cancer pain was seen in mice receiving 5-FC alone, radiotherapy alone, or 5-FC with radiation treatment. Previous study of painful bone cancers has shown that reductions in bone cancer pain from sarcoma, melanoma, and colon adenocarcinoma tumors are associated with treatments that inhibit cancer-induced osteolysis and reduce tumor burden (19,20,25,26,34). Surprisingly, in this investigation, radiation treatment alone and CD/5-FC therapy combined with radiation significantly reduced breast cancer -induced osteolysis and tumor burden but did not influence pain behaviors.…”
Section: Discussioncontrasting
confidence: 62%
“…Based on unpublished data from preliminary in vivo dose-finding experiments, inoculation with 10 4 breast carcinoma cells was determined to provide tumor progression and pain behavior development as described previously in experimental models of bone cancer pain (19,20). 4T1 cells were transduced, as described previously (4), with a fusion gene encoding the extracellular and transmembrane domains of the human nerve growth factor receptor (NGFR) and the cytoplasmic portion of CD y .…”
Section: Methodsmentioning
confidence: 99%
“…While most of the studies investigating radiation effects on osteoblasts use much higher doses than we used, it has been demonstrated that 2 Gy of X rays results in reduced numbers of pre-osteoblasts and inhibits their differentiation in vitro (27). Relatively few studies have examined osteoclasts (and changes in bone resorption) after irradiation (13,28,29). None of these studies have documented significant increases in osteoclast numbers after irradiation, nor has a change in the expression of some important regulators of osteoclast activity [namely receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG)] been documented relative to nonirradiated controls from mouse bone marrow cultured with 2 Gy carbon-ion-and γ-irradiated pre-osteoblasts (12).…”
Section: Discussionmentioning
confidence: 99%
“…176 When sarcoma cells (10 5 in 20 μl) were implanted into mouse femurs to examine the effects of 20-Gy and 30-Gy radiation as a means to control cancer pain, these radiation therapies effectively decreased cancer-induced osteolysis, reduced tumor size by 75%, and decreased bone cancerrelated pain. [57][58][59] Radiation therapy also successfully controlled pain and skeletal fractures associated with femoral implantation of 4T1 breast carcinoma cells into mice. 59 These studies demonstrated that radiation therapy effectively decreased cancer-induced pain by direct effects on tumor cells.…”
Section: Models Of Cancer Painmentioning
confidence: 99%
“…59 These studies demonstrated that radiation therapy effectively decreased cancer-induced pain by direct effects on tumor cells. 57,58 Support for the effects of radiation therapy also comes from studies in which transplantable hepatocellular carcinoma cells, HCa-1, were injected into the periosteal membrane of the foot dorsum in C3H/ HeJ mice. 129,149 In these studies, mice treated with radiotherapy showed decreased objective levels of pain (decrease mechanical hyperalgesia) beginning 3 d after irradiation compared with that in control nonradiated mice.…”
Section: Models Of Cancer Painmentioning
confidence: 99%